Uma Lengge: A Local Wisdom of Plants and Environmental Resources Utilisation in Bima Traditional House Architecture, West Nusa Tenggara - Maryanti Maryanti; Immy Suci Rohyani; Kurniasih Sukenti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Uma Lengge is a traditional house of Bima tribe located at Maria Village, Sumbawa Island, West Nusa Tenggara, with main raw material consisting of species of woods, bamboos and reeds. As one of the cultural heritage in West Nusa Tenggara, a study that support theÃÂ cultural preservation efforts is needed, including the preservation on plants used in its construction. This ethnobotanical research aims to reveal the local wisdom and other ethnobotanical aspects contained in Uma Lengge architecture. This descriptive exploratory research applied qualitative and quantitative ethnobotanical research methods based on data collection carried out through observation, interviews and documentation. Informants selection used purposive sampling and snowball sampling method. Qualitative and quantitative data were analyzed descriptively based on the observations, interviews, and calculations of Reported Use (RU) and Index of Cultural Significance (ICS). The result showed that local wisdom contained in Uma Lengge architecture is still applied by the local people from generation to generation in term of plants utilisation in Uma Lengge construction, ancient habits, customs, and the preservation of annual traditions or rituals that have good values to be passed on. There are 11 species used as materials in Uma Lengge constuction, namely Bambusa vulgaris, Artocarpus heterophyllus, Dalbergia latifolia, Tectona grandis, Areca catechu, Gossampinus malabarica, Imperata cylindrica, Ficus benjamina, Cocos nucifera, Gigantochloa apus and Swietenia macrophylla. Plant utilisation in Uma Lengge is used in 10 categories: poles, floors, beams, sloofs, roofs, unifiers, rodent insulation boards, wind breakers, stairs and fences. Conservation efforts for species involved in Uma Lengge construction need to be done, especially for species with limited availability. It is recommended that this cultural site should get more attention and efforts to preserve the cultural heritage along with all local wisdom related to plants and environmental utilisation contained in it.